Morphofunctional characteristics of the tomato male gametophyte under conditions of viral pathogenesis - T. I. Saltanovish; L. I. Andronic; L. P. Antosh; A. N. Doncila (Овощи России, 2021)
Relevance. The action of viral phytopathogens changes the quality of the male gametophyte, which ultimately leads to a decrease in plant productivity. So, information on the features of the variability of morphofunctional characteristics of the microgametophyte becomes topical. Taking into account the expression of a part of the plant genome in pollen, the male gametophyte can be used as a reliable system for assessing the response of genotypes to the action of viral pathogens. Presuming that the problems of variability of characteristics of the male gametophyte in conditions of viral pathogenesis have not been enough studied, as well as the main factors determining the variability have not been identified, the aim of the research was to study the effect of viral phytopathogens on the male gametophyte characters in tomato.Material and methods. Hybrids F1 and varieties of tomato were used in the experiments. Plants were grown in a greenhouse. They were inoculated with tobacco mosaic virus (TMV) or tomato aspermia virus (TAV) in the 4-5 leaf phase. To determine the quality of pollen, flowers of control and infected plants were collected; pollen was isolated and sown on a nutrient medium. The preparations were analyzed under microscope. The viability of the pollen and the length of the pollen tubes were assessed, and the ratio of these indicators was calculated.Results. Infection of plants with viruses changes some functional characteristics of the male gametophyte. The responses manifested as stimulation, inhibition, or neutral effect. The main sources of variability in characters of pollen were the genotype and viral agents. In viral pathogenesis, unequal indicators of pollen grains were found in terms of the rate of germination and growth of pollen tubes (PT). Analysis of the heritability coefficients of the ratio of pollen viability and PT length (experiment / control) revealed positive dominance and overdominance in 70% of cases. Genotypes have been identified that combine a high level of viability when infected with different viruses. The prospect of their use in further research is proposed.